SUN-418 Patterns of Thyroid Disease in Basrah, Iraq. Retrospective Study - Mansour, Abbas Ali (J Endocr Soc, 2020)
Background: Data on thyroid disease epidemiology in the Middle East are scanty and anecdotal. This study aimed to assess the pattern of thyroid disease seen in Faiha Specialized Diabetes, Endocrine and Metabolism Center (FDEMC) in Basrah,Southern Iraq. Methods Retrospective observational study of database retrieval from the FDEMC a tertiary care Center in Basrah for the period of September 2008 to January 2019. Included all adults non pregnant 18 years or older. Results Total enrolled patients 17878; of them 4174(23.3%) men and 13705(76.7 %) women. There were 2229(12.5%) patients with hypothyroidism (83.0% women), with subclinical hypothyroidism observed in 364 out of 2229 with hypothyroidism(16.3%). We found 1087 (6.1%) patients with hyperthyroidism (67.7% women) and subclinical hyperthyroidism observed in 92 of 1087 hyperthyroidism (8.4%). Thyroid nodularity was seen in 944 (5.2%) patients (807 women in 85.5%). Thyroidectomy was done in 776(4.3%). Differentiated thyroid cancer was seen in 77 (0.4%). Conclusion: Hypothyroidism was double that of hyperthyroidism. Cross-sectional community-based study can give more information on the epidemiology of thyroid disease in Iraq.Iodine status needed studded in the future. Keywords: Hyperthyroidism, hypothyroidism,autoimmune thyroid disease, Iraq.